Human Blood Non-Classical/Classical Monocyte Cells Are Heterogeneously Presented in Severe COVID-19 and Correlate with Disease Activity - Danhong Zhou; Yu Shen; Suxian Jing; Dong Qiu; Yang Wang; Qiuxia Qu; Cheng Chen (Journal of Innate Immunity)
Introduction: COVID-19 is highly heterogeneous, ranging from cases with mild disease with an almost asymptomatic carrier to severe cases, in which the disease evolves rapidly. A better understanding of monocyte response during SARS-CoV-2 infection would highlight potential biomarkers and establish other possible approaches for severe cases. Methods: The study group consisted of 32 COVID-19 patients and 18 health controls from June 2023 to March 2024. The COVID-19 patients were further classified as mild and severe illnesses based on World Health Organization (WHO) criteria. For flow cytometric analysis, 50 µL of peripheral blood and 1 µL of specific monoclonal antibodies were added to each cytometric tube for surface marker detection. Results: Here, the promising finding was that the blood non-classical/classical monocyte (NC/CL) subset was skewed toward NChighCLlow and NClowCLhigh clusters among the severe COVID-19 patients. The NChighCLlow cluster in severe COVID-19 displayed a distinct clinical phenotype, implying a higher 7-day disease progression rate (p = 0.019) and a worse 28-day survival (p = 0.026). Moreover, the secretion of IL-1β and IFN-γ was primarily attributed to CL subset in monocytes, while IL-6 was secreted mainly by NC subset. Conclusion: As supported, regarding cytokine profile in context of SARS-CoV-2 infection, it was identified that circulating NC cells are proinflammatory cells most related to regulatory cells, while CL subset displayed an effective capacity to virus. These findings have implications toward optimizing evaluation in severe COVID-19, and developing strategies that target altered balance of NC/CL cell subsets.